2020
DOI: 10.1111/jmi.12881
|View full text |Cite
|
Sign up to set email alerts
|

The mysterious life of the plant trans‐Golgi network: advances and tools to understand it better

Abstract: By being at the interface of the exocytic and endocytic pathways, the plant trans-Golgi network (TGN) is a multitasking and highly diversified organelle. Despite governing vital cellular processes, the TGN remains one of the most uncharacterized organelle of plant cells. In this review, we highlight recent studies that have contributed new insights and to the generation of markers needed to answer several important questions on the plant TGN. Several drugs specifically affecting proteins critical for the TGN f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…However, double labeling experiments with unspecific (the styryl dye FM4‐64) and specific (the BRI1‐YFP, brassinosteroid insensitive1 receptor) endocytic tracers and the fluorescent TGN markers (VHA‐a1‐RFP; ST‐GFP) have convincingly demonstrated that the TGN also acts as an endocytic compartment and functions as the early endosome (EE) in plants (Viotti et al ., 2010). The TGN/EE has a discrete set of marker proteins and is equipped with a V‐ATPase type proton pump which serves to acidify this organelle (for details, see the recent reviews Elliott et al ., 2020; Renna & Brandizzi, 2020).…”
Section: The Trans‐golgi Network (Tgn)mentioning
confidence: 99%
“…However, double labeling experiments with unspecific (the styryl dye FM4‐64) and specific (the BRI1‐YFP, brassinosteroid insensitive1 receptor) endocytic tracers and the fluorescent TGN markers (VHA‐a1‐RFP; ST‐GFP) have convincingly demonstrated that the TGN also acts as an endocytic compartment and functions as the early endosome (EE) in plants (Viotti et al ., 2010). The TGN/EE has a discrete set of marker proteins and is equipped with a V‐ATPase type proton pump which serves to acidify this organelle (for details, see the recent reviews Elliott et al ., 2020; Renna & Brandizzi, 2020).…”
Section: The Trans‐golgi Network (Tgn)mentioning
confidence: 99%
“…Plant TGN/EE, comprising of blebbing, tubular-reticular membranes with clathrin-coated vesicles (CCV), is a distinct organelle arises from cisternal maturation of the trans most Golgi cisterna (Golgi-associated TGNs, GA-TGNs), while GI-TGNs (Golgi-released independent TGNs) derived from GA-TGN are away and behave independently from the Golgi apparatus ( Viotti et al, 2010 ; Kang et al, 2011 ; Uemura et al, 2014 , 2019 ). TGNs are sub-compartmentalized molecularly and functionally ( Heinze et al, 2020 ; Renna and Brandizzi, 2020 ), and most recently, two subregions of a single TGN, namely, the secretory trafficking zone and the vacuolar trafficking zone, responsible for distinct cargo sorting are proposed ( Shimizu et al, 2021 ). Application of specific Vacuolar H + -ATPase (VHA-ATPase) inhibitor Concanamycin A causes the loss of TGN/EE identity possibly by increasing its lumenal pH, this leads to vacuolation of TGN/EE, Golgi cisternae bending, and Golgi fragmentation in BY-2 cells ( Robinson et al, 2004 ).…”
Section: Post-golgi Traffickingmentioning
confidence: 99%
“…As highlighted by Renna and Brandizzi (2020), the numerous tools developed (reverse genetics, proteomics, chemical inhibitors, superresolution live‐cell imaging etc.) together with lipidomics (Wattelet‐Boyer et al ., 2016) are now at hand to unravel the different functions of the TGN, to determine all the key actors and functional machineries in the different subdomains involved in cargo sorting and transport, and finally to investigate the homeostatic regulation of the TGN in various environmental conditions.…”
Section: Snares In the Secretory Pathwaymentioning
confidence: 99%